Which psychophysical colour vision test to use for screening in 3–9 year olds? - Manca Tekavčič Pompe; Branka Stirn Kranjc (Zdravniški Vestnik, 2012)
Background: To compare 4 psychophysical colour vision tests in children and to decide which test is most suitable for screening in pre-school and early school-age period. Methods: The first test used was a modified Ishihara plates test (Handaya Co. Ltd., Tokyo). The second test ”Colour vision testing made easy” (CVTME) (T. L. Waggoner, 1994) is also based on pseudoisochromatic plates with child-friendly symbols. The third test used was the ”Neitz test of colour vision” (WPS, 2001) and the fourth was ”Mollon-Reffin Minimalist test” (MRM) (version 0.7, 1994). In the first three tests, the child had to tell what he or she saw in the picture, whereas in the fourth test the child had to pick the coloured button among distractors. Thirty-seven children (19 girls and 18 boys) from 3–9 years of age with normal colour vision (at least one test should be performed without errors) were tested. The number of errors in each of the first 3 tests was registered, whereas in the MRM test the least saturated button distinguished among distractors was registered. Specificity was calculated for each test. Every child was also asked which was his or her favourite test. Results: 16/37 children made one or more errors in the modified Ishihara test, among them all children under the age of 5 years. Nine children made 1 error, three made 2, two made 3 and two children made 5 errors. 8/37 children made 1–3 mistakes in the CVTME test. Four children made one mistake, three made two and one child made three mistakes. All tested children made at least one mistake in the Neitz test. All gave a wrong description for the figure in the 6th position of the test. Two 3-year-old girls were not able to perform the test. The MRM test was not performed in full by 10/37 children. Most of these children made errors in the tritan colour vision axis. The highest specificity in all 3 age groups was calculated for CVTME test and MRM test. 28/37 children chose the MRM test as their favourite. Conclusions: The modified Ishihara colour test has turned out to be too difficult and therefore unreliable in the youngest children. For children under 5 years of age CVTME was more reliable in this study. For all ages the MRM test was the easiest to perform. Most children in this study subjectively preferred the MRM test.